2013
DOI: 10.1177/1550059412465607
|View full text |Cite
|
Sign up to set email alerts
|

The Resting Electrophysiological Profile in Adults With ADHD and Comorbid Dysfunctional Anger

Abstract: Although dysfunctional anger is not a Diagnostic and Statistical Manual of Mental Disorders (Fourth Edition, Text Revision [DSM-IV-TR]) diagnosis, it sometimes presents as a primary clinical complaint and as a comorbid feature in a subset of adults with attention-deficit/hyperactivity disorder (ADHD). No known studies have examined electroencephalographic (EEG) profiles in adults with comorbid dysfunctional anger and ADHD (ADHD + anger). Resting EEG was recorded in 14 ADHD + anger adults (11 males) and 14 cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 59 publications
2
15
0
1
Order By: Relevance
“…Increased beta responses mainly over frontal, central and parietal brain regions were related to negative emotions elicited by angry facial expressions [54] or pictures with negative emotional content [55]. Similarly, ADHD adults with dysfunctional anger and emotional dysregulation showed more beta activity than a control group [41]. The processing of negative emotions seems to be associated with increased beta activity and may thus be related to delinquent behavior.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Increased beta responses mainly over frontal, central and parietal brain regions were related to negative emotions elicited by angry facial expressions [54] or pictures with negative emotional content [55]. Similarly, ADHD adults with dysfunctional anger and emotional dysregulation showed more beta activity than a control group [41]. The processing of negative emotions seems to be associated with increased beta activity and may thus be related to delinquent behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive beta activity was not limited to frontal areas in our study, but appeared also on central and parietal electrodes. This might indicate a hypervigilant state, being associated with overreactions to relatively harmless stimuli [41], which may in turn predispose to delinquent behavior. Therefore, excessive beta activity over frontal, central and parietal brain regions might constitute a risk-factor for delinquent behavior in subjects with ADHD symptomatology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There has been some consistent evidence that ADHD is linked to relative greater left frontal cortical activity (Baving, Laucht, & Schmidt, ; Hale et al, ; Hale, Smalley et al, 2009; Keune et al, ; Keune, Wiedemann, Schneidt, & Schonenberg, ), yet—as always in frontal asymmetry research—there is also some unsupportive evidence (Gordon, Palmer, & Cooper, ) and a contradictory finding (Jaworska et al, ). Of particular importance for the present context, Keune et al () analyzed ADHD and depressive symptoms and showed that ADHD mediated the relation between relative greater left frontal alpha activity and depression.…”
Section: Frontal Asymmetry Comorbid Anxiety and Other Disordersmentioning
confidence: 99%